2011
DOI: 10.3892/ijo.2011.1097
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β-induced protein (TGFBI) suppresses mesothelioma progression through the Akt/mTOR pathway

Abstract: As an uncommon cancer, mesothelioma is very hard to treat with a low average survival rate owing to its usual late detection and being highly invasive. The link between asbestos exposure and the development of mesothelioma in humans is unequivocal. TGFBI, a secreted protein that is induced by transforming growth factor-β in various human cell types, has been shown to be associated with tumorigenesis in various types of tumors. It has been demonstrated that TGFBI expression is markedly suppressed in asbestos-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…These include high mobility group box 1 (HMGB1) and other cytokines, reactive oxygen species, and growth factors that promote sustained cell injury, inflammation, and DNA damage and stimulate cell growth, leading to fibrosis and/or carcinogenesis. 65 72 …”
Section: Environmental Exposurementioning
confidence: 99%
“…These include high mobility group box 1 (HMGB1) and other cytokines, reactive oxygen species, and growth factors that promote sustained cell injury, inflammation, and DNA damage and stimulate cell growth, leading to fibrosis and/or carcinogenesis. 65 72 …”
Section: Environmental Exposurementioning
confidence: 99%
“…The C-terminal fragment of TGFBI induces human osteosarcoma and lung carcinoma cell apoptosis [ 23 , 24 ]. TGFBI knockdown promotes the proliferation of mesothelioma cells [ 25 ]. TGFBI evokes apoptosis of ovarian carcinoma cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, overexpression of TGFBI in renal, pancreas or colon cancer cells induces cell migration and increases metastatic potential [22]. Others have shown that ectopic expression of TGFBI in transformed cells significantly suppresses tumorigenicity in multiple tumors, indicating that frequent downregulation of TGFBI is involved in tumor progression [21], [23]. Therefore, depending on the tissue, TGFBI functions as a promoter or suppressor of cancer growth [22].…”
Section: Introductionmentioning
confidence: 99%